2022
DOI: 10.3390/rs14112632
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Climate Zones of Iran Using Hybrid Interpolation Methods

Abstract: Climate plays a key role in ecosystem services. Understanding microclimate change can be a significant help in making the right decision for ecosystems and buffering the effects of global warming. Given the large distances between meteorological stations and the changes in the climate variables within short distances, such variations cannot be detected just by using observed meteorological data. This study aimed at determining the spatial structure of the mean annual temperature, the annual average precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Our analysis is consistent with the results ofAlizadeh-Choobari and Najafi (2018) who identified six distinct climate zones in Iran based on the analysis of precipitation data over 50 synoptic stations across Iran. The identification of the semi-arid, arid and hyperarid climates in many parts of Iran is also consistent with the results of AsadiOskouei et al (2022) who concluded that large parts of Iran are characterized by an arid climate. Based on the Köppen-Geiger climate classification, Raziei (2022) also concluded that 33.5% of Iran is covered by dry and 44.6% of it by semi-arid climate.The highest monthly and seasonal precipitation over Iran occur in March (48.6 mm) and winter (134.1 mm), respectively, while the highest monthly and seasonal temperature occur in July (29.1 C) and summer (28 C), respectively.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Our analysis is consistent with the results ofAlizadeh-Choobari and Najafi (2018) who identified six distinct climate zones in Iran based on the analysis of precipitation data over 50 synoptic stations across Iran. The identification of the semi-arid, arid and hyperarid climates in many parts of Iran is also consistent with the results of AsadiOskouei et al (2022) who concluded that large parts of Iran are characterized by an arid climate. Based on the Köppen-Geiger climate classification, Raziei (2022) also concluded that 33.5% of Iran is covered by dry and 44.6% of it by semi-arid climate.The highest monthly and seasonal precipitation over Iran occur in March (48.6 mm) and winter (134.1 mm), respectively, while the highest monthly and seasonal temperature occur in July (29.1 C) and summer (28 C), respectively.…”
supporting
confidence: 90%
“…For example, Alizadeh‐Choobari and Najafi (2018) identified six distinct climate zones in Iran based on the analysis of precipitation data over 50 synoptic stations across Iran. More recently, Asadi Oskouei et al (2022) have analysed ground‐based measurements over many stations across Iran and concluded that large parts of Iran are characterized by a hot and arid climate. Raziei (2022) has identified many distinct types of climates in Iran and argued that the diverse climate of Iran is caused by topographic diversity, a large latitudinal range and the land‐sea contrast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties in the InVEST model predictions are due to a range of simplified presumptions about intricate socioecological processes (based on the Budyko hydrological framework) and the climate input errors (especially annual precipitation) [72]. The climate data utilized in this investigation were obtained by interpolating actual observations, and although data quality controls were performed in the data processing, the spatial heterogeneity of meteorological variables prevented the interpolated data from presenting local microclimates [73]. In addition, our study visualizes differences in the relationship between different sub-basins and WYs, with the selected drivers varying dramatically in explanatory power across sub-basins (Figure 7), for example, not explaining well the drivers of WYs in the Beiluo Basin.…”
Section: Limitations and Future Work Directionsmentioning
confidence: 99%
“…In the realm of hydrological research, the application of RFA stands as an indispensable tool for assessing and quantifying the occurrence of extreme precipitation events across varied geographical regions (Yamada and others 2019). In Iran, a country characterized by diverse climatic zones and topographical features, the necessity for conducting RFA of precipitation data emerges as a paramount academic pursuit (Asadi Oskouei et al 2022). This imperative stems from the intrinsic complexities inherent in Iran's hydrological regime, compounded by the sparse distribution of meteorological stations, and the heightened vulnerability of its population to the impacts of extreme weather phenomena (Maghsoudi 2020).…”
Section: Introductionmentioning
confidence: 99%